Evaluation of the Mangrove Ecosystem Conditions in Wundulako Sub-District and Their Consequences on Insect Diversity - Ramad Arya Fitra; Bardan Bulaka; Reski Hidayanti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Insect diversity is believed to serve as one of the bioindicators for the condition of an ecosystem.In this investigation, data pertaining to the density of mangroves were collected by extracting samples from designated stations. This was achieved by utilizing the transect line and quadrat approach, known as the Transect Line Plot method. The data were gathered through observation plots measuring 10x10 m2, aiming to document the mangrove vegetation categorized as trees.At each station, any insect samples identified were subjected to characterization based on their morphological traits, utilizing an insect identification guide.Based on the research results, there are six mangrove species among themfindings obtained through field research at four observation station sites unveiled the existence of six distinct variations of mangrove forest types within the coastal region of Wundulako District. Among these, four types belonged to the Rhizophoraceae family, specifically Rhizophora apiculata, Rhizophora Mucronata, Ceriopstagal, and Bruguiera Gymnorrhiza, . Additionally, there was one species from the Combretaceae family, Lumnitzeraand Racemosa, and another from the Sonneratiaceae family, Sonneratia Alba. Generally, the density of the mangrove ecosystem was determined to be ranging from moderate to dense.Furthermore, a scrutiny of the insect diversity index yielded values of 1.23 for Station I, 1.39 for Station II, 1.36 for station III, and 1.69 for sStation IV. Based on the findings derived from the research, it is plausible to conclude that the condition of the mangrove ecosystem in Wundulako District across the four stations varies from limited to extensive. Additionally, the outcomes from the insect diversity index suggest a relatively reduced level of insect diversity.